Whale-Watching Management: Assessment of Sustainable Governance in Uramba Bahía Málaga National Natural Park, Valle del Cauca - Soto-Cortés, Laura V.; Luna-Acosta, Andrea; Maya, Diana Lucía (Frontiers in Marine Science, 2021)
As the growth of the whale-watching activity increases rapidly around the world, the challenge of responsible management and sustainability also rises. Without suitable management, operators may try to maximize their own profits by breaking the rules, which may negatively affect cetaceans. In this paper, the applicability of conditions for sustainability governance in humpback whale-watching was evaluated. To achieve this purpose, semi-structured interviews were conducted in Uramba Bahía Málaga National Natural Park, Colombia. Results of this study showed that humpback whale-watching is characterized by unevenness in connections with markets, income inequality and the distribution of operators across several villages and cities. The combination of which restricts cooperation between operators. Nevertheless, there are informal agreements among the operators, and some operators are motivated to form associations. Besides, environmental entities have been responsible of regulation in lack of community-based management. However, this still does not achieve effective enforcement of the rules. Stakeholders (communities and government authorities) must mediate trust and reciprocity among operators to improve the situation. It is important to involve all operators to fill gaps in the limited government monitoring capacity and absence of sanctions. This is relevant to continue monitoring the evolution of the whale-watching in this and other Marine Protected Areas, so that the sustainability of the activity is not affected in the future.